2018
DOI: 10.3892/ol.2018.9501
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis of adult patients with acute megakaryocytic leukemia

Abstract: Acute megakaryocytic leukemia (AMKL) is a rare subtype of acute myeloid leukemia (AML), which is challenging to diagnose due to frequent myelofibrosis (MF) and a low percentage of blast cells. In the present study, clinical characteristics and experimental observations in 9 adult patients diagnosed with AMKL, who were recruited by the Sino-U.S. Shanghai Leukemia Co-operative Group, were analyzed in order to summarize the diagnostic experience and provide recommendations on diagnosing AMKL. All the patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…CD41 is used as a specific HSC marker during development in zebrafish embryos, and knockdown of tpd52 reduced the mRNA level of CD41 as well as the number of CD41 + cells in CHT (Figure 4C,D). CD41 is also known as a marker for myeloid‐biased haematopoietic stem cells, 28 and it is highlighted as a novel diagnostic molecule or therapeutic target in leukaemia 29 . Just as the expression of CD41 is decreased at tpd52‐MO‐injected embryos, similar pattern was observed in the human database.…”
Section: Discussionmentioning
confidence: 64%
“…CD41 is used as a specific HSC marker during development in zebrafish embryos, and knockdown of tpd52 reduced the mRNA level of CD41 as well as the number of CD41 + cells in CHT (Figure 4C,D). CD41 is also known as a marker for myeloid‐biased haematopoietic stem cells, 28 and it is highlighted as a novel diagnostic molecule or therapeutic target in leukaemia 29 . Just as the expression of CD41 is decreased at tpd52‐MO‐injected embryos, similar pattern was observed in the human database.…”
Section: Discussionmentioning
confidence: 64%
“…AMKL belongs to acute myeloid leukemia, not otherwise specified, acute megakaryoblastic leukemia according to the World Health Organization classification 2017, or M7 according to the French-American-British (FAB) system. AMKL is defined as an AML with >20% blasts, of which >50% belong to the megakaryocyte lineage [ 7 – 10 ]. AMKL comprises 4–15% of AML in children [ 11 , 12 ], but in adults, AMKL occurs in <1% of AML patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deficient expression of CD11a has been reported as another marker of AMKL [ 17 ]. Expression of the stem cell markers is inconsistent in AMKL [ 10 , 18 ]. Histopathologic features of MPO-negative AMKL reveal marked pleomorphism of neoplastic cells, ranging from myeloblast-like small round cells to large cells with an abundant cytoplasm, in the fibrotic bone marrow tissue [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, there were 7 patients who had moderate and extensive myelofibrosis resulting in dry tap and inaccurate diagnosis of AML-M7 (9). Another study on AML-M7 also found that dry taps suggested a bone marrow biopsy to support the diagnosis (10).…”
Section: Disscusionmentioning
confidence: 97%